Novel CHK1 inhibitor MU380 exhibits significant single-agent activity in TP53-mutated chronic lymphocytic leukemia cells - Boudny, Miroslav; Zemanova, Jana; Khirsariya, Prashant; Borsky, Marek; Verner, Jan; Cerna, Jana; Oltova, Alexandra; Seda, Vaclav; Mraz, Marek; Jaros, Josef; Jaskova, Zuzana; Spunarova, Michaela; et al. (Haematologica, 2019)
Introduction of small-molecule inhibitors of B-cell receptor signaling and BCL2 protein significantly improves therapeutic options in chronic lymphocytic leukemia. However, some patients suffer from adverse effects mandating treatment discontinuation, and cases with TP53 defects more frequently experience early progression of the disease. Development of alternative therapeutic approaches is, therefore, of critical importance. Here we report details of the anti-chronic lymphocytic leukemia single-agent activity of MU380, our recently identified potent, selective, and metabolically robust inhibitor of checkpoint kinase 1. We also describe a newly developed enantioselective synthesis of MU380, which allows preparation of gram quantities of the substance. Checkpoint kinase 1 is a master regulator of replication operating primarily in intra-S and G2/M cell cycle checkpoints. Initially tested in leukemia and lymphoma cell lines, MU380 significantly potentiated efficacy of gemcitabine, a clinically used inducer of replication stress. Moreover, MU380 manifested substantial single-agent activity in both TP53-wild type and TP53-mutated leukemia and lymphoma cell lines. In chronic lymphocytic leukemia-derived cell lines MEC-1, MEC-2 (both TP53-mut), and OSU-CLL (TP53-wt) the inhibitor impaired cell cycle progression and induced apoptosis. In primary clinical samples, MU380 used as a single-agent noticeably reduced the viability of unstimulated chronic lymphocytic leukemia cells as well as those induced to proliferate by anti-CD40/IL-4 stimuli. In both cases, effects were comparable in samples harboring p53 pathway dysfunction (TP53 mutations or ATM mutations) and TP53-wt/ATM-wt cells. Lastly, MU380 also exhibited significant in vivo activity in a xenotransplant mouse model (immunodeficient strain NOD-scid IL2Rγnull ) where it efficiently suppressed growth of subcutaneous tumors generated from MEC-1 cells.
Keywords: myši inbrední NOD; pyrazoly; deoxycytidin; Apoptosis; regulace genové exprese u nádorů; Humans; inhibitory proteinkinas; Antimetabolites, Antineoplastic; Tumor Cells, Cultured; pyrimidiny; Cell Cycle; Biomarkers, Tumor; nádorový supresorový protein p53; Mice, Inbred NOD; myši SCID; mutace; Checkpoint Kinase 1; Drug Synergism; Female; Mice, SCID; lidé; chemorezistence; proliferace buněk; myši; zvířata; Gemcitabine; chronická lymfatická leukemie; Piperidines; synergismus léků; apoptóza; nádorové buňky kultivované; Mice; nádorové biomarkery; Leukemia, Lymphocytic, Chronic, B-Cell; xenogenní modely - testy protinádorové aktivity; Protein Kinase Inhibitors; ženské pohlaví; Deoxycytidine; Cell Proliferation; protinádorové antimetabolity; checkpoint kinasa 1; Xenograft Model Antitumor Assays; piperidiny; Animals; Mutation; Pyrimidines; Gene Expression Regulation, Neoplastic; Pyrazoles; buněčný cyklus; Drug Resistance, Neoplasm; gemcitabin; Tumor Suppressor Protein p53